Astrocyte glutamate uptake impacts [18F]FDG‐PET signal: Neuroimaging / animal imaging. (7th December 2020) - da Rocha, Andreia Silva; de Souza, Débora Guerini; Bellaver, Bruna; Fontana, Igor C.; Machado, Luiza Santos; Venturin, Gianina Teribele; Greggio, Samuel; da Costa, Jaderson Costa; Souza, Diogo O.; Zimmer, Eduardo R.
Abstract: Background: The role of astrocytes on brain functioning has become an important topic of debate. In this regard, an issue that still remains controversial is the astrocytes contribution to glucose brain metabolism and, therefore, to the uptake of 2‐Deoxy‐2‐[ 18 F]Fluoroglucose([ 18 F]FDG) detected by positron emission tomography(PET). For many years, it was widely assumed that the brain [ 18 F]FDG‐PET signal directly reflects the neuronal use of glucose, overlooking the possible participation of other brain cells. Recently, rodent and human studies have demonstrated that astrocytes may contribute to [ 18 F]FDG‐PET signal. To further explore these early findings, here, we used a pharmacological challenge on rodents. Clozapine was selected because it is known to decrease, on astrocytes, glutamate transport and the glutamate transporter 1 (GLT‐1) levels, an important trigger for glucose uptake in astrocytes. Methods: Clozapine was administered for six weeks (25‐35mg/kg) to adult Wistar rats. Glucose brain metabolism was assessed using [ 18 F]FDG‐microPET before and after the treatment. [ 3 H]D‐Aspartate uptake was evaluated on brain slices. [ 3 H]Glutamate release was analyzed on synaptosomal preparations. [ 3 H]D‐Aspartate and [ 3 H]2‐Deoxyglucose uptake were analyzed on primary cortical astrocytic and neuronal cultures treated with clozapine (50uM) for 48h. Immunocontent and expression of GLT‐1 and Glutamate‐Aspartate Transporter(GLAST) were assessed on the cortical tissue and cell cultures. Results: Clozapine treatment significantly reduced [ 18 F]FDG metabolism in the cerebral cortex, hippocampus, and striatum of adult rats. In addition, clozapine decreased cortical glutamate transport in brain slices – indexed by [ 3 H]D‐Aspartate uptake – and reduced the cortical immunocontent and expression of GLT‐1. Astrocytic cultures treated with clozapine presented a decline on GLT‐1 density, [ 3 H]D‐Aspartate uptake and [ 3 H]2‐Deoxyglucose uptake, while the neuronal cultures presented no changes. Conclusion: Here, we present microPET data showing that a challenge with clozapine causes a reduction on [ 18 F]FDG signal in brain regions presenting high GLT‐1 density. Our cell culture findings indicate that astrocytes are, at least partially, the cells underlying the brain glucose metabolism response to clozapine. These results corroborate previous studies that highlight the need for a reevaluation in the way that brain [ 18 F]FDG‐PET data is interpreted. Additionally, clozapine is a drug approved for clinical use, therefore, these findings could have high translational implications.